MOFs (Metal-Organic Frameworks) mixed matrix membrane for nitrogen-oxygen separation and preparation method of MOFs mixed matrix membrane
By growing MOFs in situ on the membrane, the preparation process of the nitrogen-oxygen separation membrane is simplified, and the complex and cost-effective preparation problems in the prior art are solved, thereby achieving efficient nitrogen-oxygen separation and clean oxygen-rich air production.
Patent Information
- Application Number
- CN202411721531.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-07
AI Technical Summary
The existing MOFs membrane modules for nitrogen-oxygen separation are complex in the preparation process and the synthesis conditions are harsh, which increases the production difficulty and cost, making it difficult to produce on a large scale.
In situ growth method was used to grow metal organic frame materials (MOFs), such as ZIF-8 and CuBTC, on PI, PSF or PIM-1 membranes, to form a hybrid matrix membrane, simplifying the preparation process.
The mixed matrix membrane prepared by this method can effectively separate nitrogen and oxygen, improve oxygen permeability and selectivity, stabilize the production of clean oxygen-rich air with an oxygen content of more than 50%, and reduce costs and energy consumption.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of membrane separation, and in particular to a MOFs mixed matrix membrane for nitrogen and oxygen separation and a preparation method thereof. Background Art
[0002] Oxygen therapy is an effective clinical means of treating respiratory diseases, and oxygen concentrators are a necessary medical auxiliary equipment. At present, the common type of medical oxygen concentrator is the pressure swing adsorption oxygen concentrator, which uses pressure swing adsorption technology to produce oxygen and can extract oxygen from the air. The medical oxygen concentrator is equipped with a molecular sieve. Under pressure, the physical adsorption technology and desorption technology of the molecular sieve are used to adsorb nitrogen in the air, and the unabsorbed oxygen will be collected. By purifying it, relatively high-purity oxygen can be obtained. The nitrogen / oxygen separation by pressure swing adsorption has a simple process flow, low process conditions, simple maintenance, and a high degree of automation. However, molecular sieves are expensive consumable materials and have high energy consumption.
[0003] Metal-organic framework materials (MOFs) are a new type of inorganic-organic hybrid microporous materials. They are one-dimensional, two-dimensional or three-dimensional mesh microporous structure skeleton crystal materials synthesized by metal ions and organic ligands through self-assembly and connection. Compared with molecular sieves, MOFs have the advantages of rich structure, large specific surface area and adjustable pore size, showing great potential in gas separation. However, the preparation process of existing MOFs membrane components for nitrogen and oxygen separation is complicated, and some MOFs have harsh synthesis conditions and need to be carried out under high temperature and high pressure, oxygen and water-free conditions, which increases the difficulty and cost of preparation and is difficult to mass produce. Summary of the invention
[0004] In view of the above-mentioned deficiencies in the prior art, an object of the present invention is to provide a MOFs mixed matrix membrane for nitrogen and oxygen separation and a preparation method thereof.
[0005] In order to achieve the above-mentioned object of the invention, the technical solution adopted by the present invention is:
[0006] Provided is a method for preparing a MOFs mixed matrix membrane for nitrogen and oxygen separation, comprising the following steps: using PI, PSF or PIM-1 as a membrane-forming material, mixing a metal organic framework material having an affinity for oxygen, and forming the membrane using an in-situ growth method.
[0007] Furthermore, the preparation method of the PSF / ZIF-8 mixed matrix membrane specifically comprises the following steps:
[0008] Dissolve Zn(NO3)2·6H2O in methanol, recorded as solution A, wherein the amount of Zn(NO3)2·6H2O added is 0-30wt%; dissolve 2-MIM in methanol, recorded as solution B, wherein the amount of 2-MIM added is 0-50wt%; mix solution A and solution B in a volume ratio of 1:1, recorded as solution C;
[0009] During the first in situ growth process, the PSF membrane was immersed in solution A and then in solution B; the second in situ growth followed the same procedure as the first in situ growth; during the third in situ growth process, the membrane that had completed the first two in situ growths was immersed in solution A and then in solution C; the fourth in situ growth followed the same procedure as the third in situ growth; the PSF / ZIF-8 mixed matrix membrane was obtained through the above in situ growth.
[0010] Furthermore, the preparation method of the PSF / CuBTC mixed matrix membrane specifically comprises the following steps:
[0011] A solvent mixture of DMF:EtOH:H2O in a certain volume ratio is recorded as solution A; BTC and triethanolamine are dissolved in solution A, recorded as solution B, wherein the amount of BTC added is 0-30wt%, and the amount of triethanolamine added is 0-30wt%; Cu(NO3)2 is dissolved in solution A, recorded as solution C, wherein the amount of Cu(NO3)2 added is 0-30wt%; Solution B and solution C are mixed in a volume ratio of 1:1, recorded as solution D;
[0012] During the first in-situ growth process, the PSF membrane was first immersed in solution A, then in solution B, and then in solution C; the second in-situ growth followed the same procedure as the first in-situ growth; during the third in-situ growth process, the membrane that had completed the first two in-situ growths was immersed in solution D; the PSF / CuBTC mixed matrix membrane was obtained through the above in-situ growth.
[0013] Furthermore, the preparation method of the PIM-1 / UiO-66 mixed matrix membrane specifically comprises the following steps:
[0014] Solvothermal synthesis of UiO-66: ZrCl4 and terephthalic acid are dissolved in DMF, with the addition amount of ZrCl4 being 0-15wt% and the addition amount of terephthalic acid being 0-60wt%; after complete dissolution, 0-1wt% of concentrated hydrochloric acid is added as a crystallizing agent, and 0-1wt% of anhydrous acetic acid is added as a regulator to obtain UiO-66 nanoparticles;
[0015] Synthesis of polymer PIM-1: TTSBI and DCTB are dissolved in DMAc, wherein the amount of TTSBI added is 0-30wt%, the amount of DCTB added is 0-30wt%, and then anhydrous potassium carbonate is added in an amount of 0-20wt%, and the reaction is carried out under an inert atmosphere to obtain polymer PIM-1;
[0016] Preparation of PIM-1 / UiO-66 mixed matrix membrane: The UiO-66 prepared above was dissolved in chloroform, recorded as solution A; PIM-1 was dissolved in chloroform, recorded as solution B; Solution A and solution B were mixed in a volume ratio of 1:1, recorded as solution C; Solution C was ultrasonically treated to prepare a PIM-1 / UiO-66 mixed matrix membrane.
[0017] Furthermore, the preparation method of the PIM-1 / ZIF-8 mixed matrix membrane specifically comprises the following steps:
[0018] Synthesis of polymer PIM-1: dissolving TTSBI and DCTB in DMAc, wherein the amount of TTSBI added is 0-30wt%, the amount of DCTB added is 0-30wt%, and then adding anhydrous potassium carbonate, the amount of which is 0-20wt%, and reacting under an inert atmosphere to obtain polymer PIM-1; preparing PIM-1 membrane from PIM-1;
[0019] 2-MIM is dissolved in methanol to prepare a 2-MIM solution, which is referred to as solution A, wherein the amount of 2-MIM added is 0-50wt%; Zn(NO3)2·6H2O is dissolved in methanol to prepare a Zn(NO3)2·6H2O solution, which is referred to as solution B, wherein the amount of Zn(NO3)2·6H2O added is 0-30wt%; Solution A and Solution B are mixed in a volume ratio of 1:1, which is referred to as solution C;
[0020] The PIM-1 membrane is immersed in solution C to obtain a single growth membrane; the above in situ growth process is repeated multiple times to obtain a PIM-1 / ZIF-8 mixed matrix membrane.
[0021] The beneficial effects of the present invention are:
[0022] The present invention prepares a nitrogen-oxygen separation mixed matrix membrane by an in-situ growth MOF method. This method does not require the preparation of MOFs and then the dispersion of MOFs particles, thus avoiding agglomeration due to uneven dispersion. The gas separation performance of the composite membrane can be regulated by increasing the growth cycle of MOFs, thereby improving the permeability of O2 and the oxygen / nitrogen selectivity, and can stably produce clean oxygen-enriched air with an oxygen content of more than 50%, thereby reducing costs and energy consumption. DETAILED DESCRIPTION
[0023] The specific implementation modes of the present invention are described below so that those skilled in the art can understand the present invention. However, it should be clear that the present invention is not limited to the scope of the specific implementation modes. For those of ordinary skill in the art, as long as various changes are within the spirit and scope of the present invention as defined and determined by the attached claims, these changes are obvious, and all inventions and creations utilizing the concept of the present invention are protected.
[0024] Example 1. Preparation of PSF / ZIF-8 mixed matrix membrane
[0025] The purchased commercial PSF membrane was washed with formalin and water and cut into circular slices with a diameter of 5 cm as the substrate for in situ crystallization of ZIF-8 at room temperature. 2.9 g Zn(NO3)2·6H2O was dissolved in 200 ml methanol, recorded as solution A; 6.48 g mmol 2-methylimidazole (2-MIM) was dissolved in 200 ml methanol, recorded as solution B; solution A and solution B were quickly mixed at a volume ratio of 1:1 at room temperature, recorded as solution C.
[0026] During the first in-situ growth process, the purchased commercial PSF membrane was immersed in methanol for 6 hours, the membrane was taken out of methanol, and the membrane was immersed in solution A and allowed to stand at room temperature for 12 hours. Subsequently, the membrane loaded with Zn(NO3)2 was immersed in solution B, allowed to stand at room temperature for 12 hours, and then washed with water, dried at room temperature for 2 hours, and then dried at 60°C for 2 hours to complete the first in-situ growth process. The second in-situ growth followed the same procedure as the first in-situ growth. During the third in-situ growth process, the membrane that completed the first two in-situ growths was first immersed in solution A, allowed to stand at room temperature for 12 hours, and then the membrane was taken out of solution A and placed in solution C containing Zn(NO3)2 and 2-MIM, allowed to stand at room temperature for 12 hours, and the membrane was taken out of the beaker, washed with water, dried at room temperature for 2 hours, and then dried at 60°C for 2 hours. The fourth in-situ growth followed the same procedure as the third in-situ growth to have a denser ZIF-8 loading on the PSF substrate.
[0027] The PSF / ZIF-8 composite membrane obtained by in-situ growth of ZIF-8 nanoparticles on the PSF membrane has an O2 permeability of 2251 barrer and an O2 / N2 selectivity of 3.0.
[0028] Example 2: Preparation of PSF / CuBTC mixed matrix membrane
[0029] The purchased commercial PSF membrane was washed with water and cut into circular slices with a diameter of 5 cm as the carrier for the in-situ crystallization of CuBTC. The DMF:EtOH:H2O solvent mixture with a volume ratio of 1:1:1 was recorded as solution A, 10g BTC and 10ml triethanolamine were dissolved in the above DMF:EtOH:H2O (solution A) with a volume ratio of 1:1:1, recorded as solution B, 16g Cu(NO3)2 was dissolved in the above DMF:EtOH:H2O (solution A) with a volume ratio of 1:1:1, recorded as solution C, and at room temperature, solution B and solution C were mixed in a volume ratio of 1:1, recorded as solution D.
[0030] In the first in-situ growth process, the membrane was first immersed in a beaker of solution A, allowed to stand at room temperature for 6 hours, the membrane was taken out of the beaker, and then immersed in a beaker containing solution B, and allowed to stand at room temperature for 12 hours. Subsequently, the BTC-loaded membrane was immersed in a beaker containing solution C, allowed to stand at room temperature for 12 hours, the membrane was taken out of the beaker, washed with water, dried at room temperature for 2 hours, and then dried at 60°C for 2 hours, and the first in-situ growth process was completed. The second in-situ growth followed the same procedure as the first in-situ growth. In the third in-situ growth process, the membrane that completed the first two in-situ growths was immersed in solution D, allowed to stand at room temperature for 12 hours, the membrane was taken out of the beaker, washed with water, dried at room temperature for 2 hours, and then dried at 60°C for 2 hours.
[0031] The PSF / CuBTC composite membrane obtained by in-situ growth of CuBTC on the surface of the PSF membrane has an O2 permeability of 2742 barrer and an O2 / N2 selectivity of 2.3.
[0032] Example 3. Preparation of PIM-1 / UiO-66 mixed matrix membrane
[0033] Solvothermal synthesis of UiO-66: 6.4 g ZrCl4 and 4.6 g terephthalic acid were dissolved in 300 mL DMF, wherein the amount of DMF added was 93 wt%, the amount of ZrCl4 added was 1.97 wt%, and the amount of terephthalic acid added was 14.2%. After complete dissolution, 0.08 wt% of concentrated hydrochloric acid was added as a crystallizing agent, and 0.03 wt% of anhydrous acetic acid was added as a regulator. After stirring for 30 min, the mixture was heated at 120 ° C for 24 h, cooled, washed once with DMF, and then washed 3-5 times with methanol, and the product was dried at 80 ° C to obtain UiO-66 nanoparticles.
[0034] Preparation of polymer PIM-1: It is synthesized by high-temperature polycondensation reaction of two monomers TTSBI and DCTB. In a three-necked flask equipped with a water separator, 17g TTSBI and 10g DCTB are dissolved in 100ml DMAc, where the DMAc addition amount is 49wt%, and then 20.7g anhydrous potassium carbonate is added, and then the reaction device is purged three times with nitrogen. Move the three-necked flask to an oil bath preheated to 155°C, stir vigorously for 2min, add 50ml toluene when the solution becomes viscous, and react for 1h under nitrogen protection. Then pour the product into methanol. Dissolve the crude polymer in chloroform and reprecipitate from methanol. Reflux the product in deionized water for 6h, and then dry it at 100°C for 48h.
[0035] Preparation of PIM-1 / UiO-66 mixed matrix membrane: The UiO-66 prepared above was dissolved in chloroform, recorded as solution A, and PIM-1 was dissolved in chloroform, recorded as solution B. Solution A and solution B were quickly mixed at a volume ratio of 1:1 at room temperature, recorded as solution C.
[0036] Solution C was ultrasonically treated for 1 h, and then the viscous slurry was transferred to a covered petri dish and dried at room temperature for 24 h to obtain a PIM-1 / UiO-66 mixed matrix membrane. The obtained membrane was soaked in methanol for 24 h, and the membrane was taken out of the beaker and dried in a vacuum oven at 120°C for 24 h.
[0037] The mixed matrix membrane was prepared by covalently linking UiO-66 and PIM-1, which showed excellent polymer-filler compatibility. The obtained PIM-1 / UiO-66 composite membrane had an O2 permeability of 395 barrer and an O2 / N2 selectivity of 5.4.
[0038] Example 4. Preparation of PIM-1 / ZIF-8 mixed matrix membrane
[0039] Preparation of polymer PIM-1: In a three-necked flask equipped with a water separator, 17g TTSBI and 10g DCTB were dissolved in 100ml DMAc, and then 20.7g anhydrous potassium carbonate was added, and then the reaction apparatus was purged three times with nitrogen. The three-necked flask was moved to an oil bath preheated to 155°C, and after vigorous stirring for 2min, 50ml toluene was added when the solution became viscous, and the reaction was carried out under nitrogen protection for 1h. The product was then poured into methanol. The crude polymer was dissolved in chloroform and reprecipitated from methanol. The product was refluxed in deionized water for 6h, and then dried at 100°C for 48h.
[0040] The PIM-1 membrane was prepared by casting method: first, the prepared PIM-1 powder was dissolved in chloroform solvent, and the impurities were filtered out after stirring for 3 hours to obtain a PIM-1 casting solution with a mass fraction of 2%; then the casting solution was poured into a culture dish with a diameter of 6 cm, covered with a glass plate, and left to stand at room temperature to allow chloroform to evaporate slowly for 24 hours; after the membrane was formed, the membrane was vacuum dried at 70°C for 24 hours to constant weight to ensure that the solvent evaporated completely. Finally, a PIM-1 membrane with a thickness of about 60 μm was obtained.
[0041] 1.65 g of 2-methylimidazole was dissolved in 30 ml of methanol to prepare a 2-MIM solution, recorded as solution A; 0.75 g of zinc nitrate hexahydrate was dissolved in 30 ml of methanol to prepare a Zn(NO3)2·6H2O solution, recorded as solution B; the two solutions were quickly mixed at a volume ratio of 1:1 at room temperature, and stirred at a medium speed for 30 min to obtain a white ZIF-8 precursor solution C.
[0042] The PIM-1 film was immersed in the precursor solution C of ZIF-8 and allowed to stand at room temperature for 12 hours. The film was then taken out, rinsed repeatedly with methanol, and dried in a vacuum oven at 60°C for 1 hour to obtain a single growth film. The above in-situ growth process was repeated many times to obtain a PIM-1 / ZIF-8 composite film, and the obtained composite film was vacuum dried at 70°C for 24 hours for use.
[0043] The PIM-1 / ZIF-8 composite membrane obtained by in-situ growth of ZIF-8 nanoparticles on the surface of PIM-1 membrane has a larger specific surface area of 1150 m 2 / g, and effectively reduced the average pore size of the polymer membrane, the O2 permeability coefficient was 1287 barrer, and the O2 / N2 selectivity was 3.7.
[0044] The present invention adopts PSF, PI or PIM-1 as membrane separation materials, and forms a mixed matrix membrane by in-situ growing MOF on an organic membrane, thereby effectively reducing the steps of preparing the mixed matrix membrane, while retaining the flexibility of MOF, allowing the feed gas to directly contact the MOF, so that the pore openings of the MOF can be used as channels for gas flow, and a membrane component is formed, forming a pre-filtration system that can produce clean oxygen-rich air and reduce energy consumption.
[0045] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0046] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A method for preparing a MOFs mixed matrix membrane for nitrogen and oxygen separation, characterized in that: The method comprises the following steps: using polymer as film-forming material, and embedding a metal organic framework material having affinity for oxygen into a polymer film matrix by an in-situ growth method; the film-forming material comprises PI, PSF and PIM-1.
2. The method for preparing a MOFs mixed matrix membrane for nitrogen and oxygen separation according to claim 1, characterized in that: The preparation method of the PSF / ZIF-8 mixed matrix membrane specifically comprises the following steps: Dissolve Zn(NO3)2·6H2O in methanol, recorded as solution A, wherein the amount of Zn(NO3)2·6H2O added is 0-30wt%; dissolve 2-MIM in methanol, recorded as solution B, wherein the amount of 2-MIM added is 0-50wt%; mix solution A and solution B in a volume ratio of 1:1, recorded as solution C; During the first in situ growth process, the PSF membrane was immersed in solution A and then immersed in solution B; the second in situ growth followed the same procedure as the first in situ growth; during the third in situ growth process, the membrane that had completed the first two in situ growths was immersed in solution A and then immersed in solution C; the fourth in situ growth followed the same procedure as the third in situ growth; the PSF / ZIF-8 mixed matrix membrane was obtained through the above in situ growth.
3. The method for preparing a MOFs mixed matrix membrane for nitrogen and oxygen separation according to claim 1, characterized in that: The preparation method of the PSF / CuBTC mixed matrix membrane specifically comprises the following steps: A solvent mixture of DMF:EtOH:H2O in a certain volume ratio is recorded as solution A; BTC and triethanolamine are dissolved in solution A, recorded as solution B, wherein the amount of BTC added is 0-30wt%, and the amount of triethanolamine added is 0-30wt%; Cu(NO3)2 is dissolved in solution A, recorded as solution C, wherein the amount of Cu(NO3)2 added is 0-30wt%; Solution B and solution C are mixed in a volume ratio of 1:1, recorded as solution D; During the first in-situ growth process, the PSF membrane was first immersed in solution A, then in solution B, and then in solution C; the second in-situ growth followed the same procedure as the first in-situ growth; during the third in-situ growth process, the membrane that had completed the first two in-situ growths was immersed in solution D; the PSF / CuBTC mixed matrix membrane was obtained through the above in-situ growth.
4. The method for preparing a MOFs mixed matrix membrane for nitrogen and oxygen separation according to claim 1, characterized in that: The preparation method of the PIM-1 / UiO-66 mixed matrix membrane specifically comprises the following steps: Solvothermal synthesis of UiO-66: ZrCl4 and terephthalic acid are dissolved in DMF, wherein the amount of ZrCl4 added is 0-15wt%, and the amount of terephthalic acid added is 0-60wt%; after complete dissolution, 0-1wt% concentrated hydrochloric acid is added as a crystallizing agent, and 0-1wt% anhydrous acetic acid is added as a regulator to obtain UiO-66 nanoparticles; Synthesis of polymer PIM-1: TTSBI and DCTB are dissolved in DMAc, wherein the amount of TTSBI added is 0-30wt%, the amount of DCTB added is 0-30wt%, and then anhydrous potassium carbonate is added in an amount of 0-20wt%, and the reaction is carried out under an inert atmosphere to obtain polymer PIM-1; Preparation of PIM-1 / UiO-66 mixed matrix membrane: The UiO-66 prepared above was dissolved in chloroform, recorded as solution A; PIM-1 was dissolved in chloroform, recorded as solution B; Solution A and solution B were mixed in a volume ratio of 1:1, recorded as solution C; Solution C was ultrasonically treated to prepare a PIM-1 / UiO-66 mixed matrix membrane.
5. The method for preparing a MOFs mixed matrix membrane for nitrogen and oxygen separation according to claim 1, characterized in that: The preparation method of the PIM-1 / ZIF-8 mixed matrix membrane specifically comprises the following steps: Synthesis of polymer PIM-1: dissolving TTSBI and DCTB in DMAc, wherein the amount of TTSBI added is 0-30wt%, the amount of DCTB added is 0-30wt%, and then adding anhydrous potassium carbonate, the amount of which is 0-20wt%, and reacting under an inert atmosphere to obtain polymer PIM-1; preparing PIM-1 membrane from PIM-1; 2-MIM is dissolved in methanol to prepare a 2-MIM solution, which is referred to as solution A, wherein the amount of 2-MIM added is 0-50wt%; Zn(NO3)2·6H2O is dissolved in methanol to prepare a Zn(NO3)2·6H2O solution, which is referred to as solution B, wherein the amount of Zn(NO3)2·6H2O added is 0-30wt%; Solution A and Solution B are mixed in a volume ratio of 1:1, which is referred to as solution C; The PIM-1 membrane is immersed in solution C to obtain a single growth membrane; the above in situ growth process is repeated multiple times to obtain a PIM-1 / ZIF-8 mixed matrix membrane.
6. A MOFs mixed matrix membrane for nitrogen and oxygen separation prepared by the method according to any one of claims 1 to 5.
Citation Information
Patent Citations
Preparation method of PIM-1 mixed matrix membrane based on amidoxime group modified UiO-66 material
CN115228311A
PIM-1 (at) ZIF-8 mixed matrix membrane based on in-situ polymerization method and preparation method of PIM-1 (at) ZIF-8 mixed matrix membrane
CN116272398A
Nitrogen / oxygen separation membrane with sterilization function and preparation method thereof
CN118403507A
High-performance anti-aging c-PIM / UiO cross-linked membrane as well as preparation method and application thereof
CN118634668A
IN204DE2013A
Cited By
Composite hollow fiber membrane based on polysulfone and MIL-160 (Al) as well as preparation method and application of composite hollow fiber membrane
CN121944842A